2023
DOI: 10.1007/s00429-023-02628-9
|View full text |Cite
|
Sign up to set email alerts
|

The right uncinate fasciculus supports verbal short-term memory in aphasia

Abstract: Verbal short-term memory (STM) deficits are associated with language processing impairments in people with aphasia. Importantly, the integrity of STM can predict word learning ability and anomia therapy gains in aphasia. While the recruitment of perilesional and contralesional homologous brain regions has been proposed as a possible mechanism for aphasia recovery, little is known about the white-matter pathways that support verbal STM in post-stroke aphasia. Here, we investigated the relationships between the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 122 publications
0
0
0
Order By: Relevance
“…However, some studies on the anatomy of the UF show that it may not link any specific areas that are important in language processing, but instead connects brain regions in the ventral and medial frontal lobe to the anterior temporal lobe and surrounding areas [ 27 ]. Despite this, research has shown a correlation between a higher fractional anisotropy in the UF with reading comprehension and verbal memory, suggesting the tract’s function in processing complex or higher-level elements of reading [ 28 , 29 , 30 ]. While the conflicting literature makes the role of UF in language and reading processes somewhat ambiguous, the tract’s anatomical position in connecting the temporal and orbitofrontal lobe along with its role in reading comprehension make it a reasonable subject of ongoing research.…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies on the anatomy of the UF show that it may not link any specific areas that are important in language processing, but instead connects brain regions in the ventral and medial frontal lobe to the anterior temporal lobe and surrounding areas [ 27 ]. Despite this, research has shown a correlation between a higher fractional anisotropy in the UF with reading comprehension and verbal memory, suggesting the tract’s function in processing complex or higher-level elements of reading [ 28 , 29 , 30 ]. While the conflicting literature makes the role of UF in language and reading processes somewhat ambiguous, the tract’s anatomical position in connecting the temporal and orbitofrontal lobe along with its role in reading comprehension make it a reasonable subject of ongoing research.…”
Section: Introductionmentioning
confidence: 99%